Seeing Through One: Kollmar-Paulenz’s Contributions to the Mongolian and Global Study of Religion(s) - Piotr Sobkowiak (AЯGOS)
The paper discusses the works by Professor Karénina Kollmar-Paulenz on Mongolian shamanism and Buddhism, embedded within the concept of a global history of religion. Contextualised within the debate on the existence of emic terms for “religion” outside of European epistemological traditions, the paper examines the disputes that Kollmar-Paulenz’s approach has engendered among scholars engaged in post-structural paradigms and presents an argument for their theoretical reconsideration.